Selective laser melting titanium alloy powder recycling process
By optimizing the pink background process and process parameters in the selection laser melting process, the Ti-6AL-4V alloy powder powder loss and cost of the Ti-6AL-4V alloy powder are solved, and the efficient, low-cost forming preparation is achieved, and the mechanics of the forming parts is improved. performance.
Patent Information
- Application Number
- CN202411513219.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
In the selected laser melting (SLM) process, the loss of Ti-6Al-4V alloy powder is large, resulting in excessive raw material costs and it is difficult for traditional processes to effectively utilize the properties of the material.
By optimizing the powder recycling process, different proportions of recycled powder and fresh powder are mixed, and numerical simulations and experiments are combined to adjust the process parameters to improve the mechanical properties of the formed parts.
It is possible to reduce the cost of metal powder raw materials, improve utilization rate, and improve the mechanical properties of formed parts while ensuring the forming quality.
Smart Images

Figure CN119346895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a selective laser melting titanium alloy powder recycling process, belongs to the field of metal 3D printing, and specifically relates to a selective laser melting titanium alloy powder recycling additive manufacturing technology. Background Art
[0002] Ti-6Al-4V alloy, also known as TC4, is an α+β titanium alloy with high strength, low density, high fracture toughness, excellent corrosion resistance and superior biocompatibility. It is lightweight and strong with high corrosion resistance and biocompatibility, and is extremely suitable for the preparation of medical implants such as human bone fixation brackets. However, due to the poor thermal conductivity, strain hardening tendency and high oxygen affinity of Ti-6Al-4V alloy, it is a challenge for traditional manufacturing processes such as forging, casting and rolling that rely on bulk raw materials. The computer-aided design (CAD) and layer-by-layer manufacturing strategy of additive manufacturing enable this technology to avoid traditional design constraints and achieve large-scale customization of parts.
[0003] Selective laser melting (SLM) is a metal additive manufacturing (AM) process that uses a scraper or roller to iteratively deposit powder at a preset layer thickness. Guided by the path of the 3D model file, the laser heat source selectively melts the powder layer to manufacture 3D parts. The rapid thermal cycle process brought about by the unique laser heat source and inert gas environment of SLM solves the limitations of the TC4 processing conditions mentioned above. At the same time, the grain refinement hardening or internal dislocation effect produced by the process can obtain high-performance complex geometric parts, saving delivery time, energy and material resources, and can significantly reduce the cost of each part in small-batch production.
[0004] However, in the actual preparation process, metal powder materials suffer from various forms of loss, including aerosol diffusion with the inert gas flow, splashing of metal droplets in the molten pool, adhesion of powder particles, and later wire cutting processing. This results in only a portion of the powder raw material being melted by the laser to form the part layer, and a considerable portion of the powder in the heat-affected zone will change its thermodynamic properties due to remelting and become waste powder, resulting in the problem of excessively high raw material costs in the SLM process. Therefore, how to reduce costs by optimizing the process parameters of recycled powder while ensuring the forming quality of Ti-6Al-4V is an important factor in promoting its application development. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a selective laser melting titanium alloy powder recycling process, aiming to explore a recycled powder raw material with different mixing ratios, based on the changes in powder properties, through different process parameter combinations to explore the scheme of optimizing the recycled powder process parameters to improve the mechanical properties of the formed parts.
[0006] The technical solution of the present invention is: a selective laser melting titanium alloy powder recycling process, using Ti-6Al-4V titanium alloy plate as a rigid substrate, Ti-6Al-4V mixed powder as a raw material, using a high-energy laser beam to selectively melt the metal powder layer and stack it layer by layer to obtain a titanium alloy formed part, the specific steps are as follows:
[0007] S1: Using the discrete element method (DEM) to refer to the actual powder characteristic parameters, a three-dimensional randomly distributed powder bed model with a filling density of 0.4 was created. The powder bed size was 1000μm*400μm*60μm, and the bottom was a rigid structure of the same size. The powder bed was imported into FLOW-3D for finite element secondary development simulation. The laser heat source used a Gaussian heat source, as shown in the following formula. Considering the complex thermal physical mechanism of the SLM process, such as heat conduction, thermal radiation, thermal convection, evaporation, melting and solidification, the Air entrainment, Density evaluation, Heat transfer and other solvers were used in parallel in the solution environment to restore the actual printing process to the greatest extent. The convection field and temperature field under the simulated dynamic molten pool were analyzed. According to the heat affected zone size data and the 70% molten pool overlap rate, the overlap between multiple melting single passes was ensured to be good, and appropriate process parameters were selected, including laser power, scanning speed, spot diameter and scanning spacing, and a process window with a molten pool depth greater than 40μm (to ensure complete bonding between layers) was selected.
[0008]
[0009] Where: q(r) is the heat flux density of a point within the radius of the Gaussian laser beam, P is the total laser power, ɑ is the laser absorptivity of the powder, ω is the radius of the Gaussian laser beam, and r is the distance between a point within the radius of the Gaussian laser beam and the center of the heat source at time t;
[0010] S2: According to the heat-affected zone size data, Ti-6Al-4V metal powder that has undergone a period of thermal cycle in the construction area of the selective laser melting preparation is collected, and the recycled powder is sieved using a 240-mesh standard experimental sample sieve. Based on the total mass of the collected recycled powder, the recycled powder is mixed in a powder mixer according to the mass fraction ratio of 0%, 20%, 40%, 60%, and 80% of the total mixed powder.
[0011] S3: Based on the relationship between the characteristics of recycled powder, process parameters and mechanical properties, the fresh powder and recycled powder are tested using an electron scanning microscope and a laser particle size analyzer. The selection range of printing parameters is adjusted according to the differences in various characteristics of the fresh powder and the recycled powder in the test results.
[0012] S4: In a 3D printing device whose printing space is a closed building cabin, a Ti-6Al-4V alloy plate is used as a rigid substrate, the basic powder layer thickness parameter is controlled by adjusting the position of a rigid scraper, mixed powders of different proportions are added in groups as raw materials, and different process parameter combinations in the selected process window are combined. High-purity argon is used as an inert protective gas, and the solid sample printing is started by laser melting the powder layer;
[0013] S5: Use a wire cutting machine to separate the solid sample, observe the surface morphology of the solid sample through an optical microscope, grind, polish and corrode the solid sample, observe the pores and metallographic structure, and optimize the process parameters. Use a mixed powder with a ratio of 0%-20% to obtain a sample with a relative density ≥99%, a hardness ≥350HV, a surface roughness Ra≤12.5μm, and a metallographic structure of needle-shaped martensite. Determine the parameter combination of laser power, scanning speed, powder thickness and scanning spacing;
[0014] Preferably, the particle size of the Ti-6Al-4V metal powder in step S1 is in the range of 15-53 μm, and the chemical composition of the powder is Al5.5-6.75wt%, V 3.5-4.5wt%, Fe≤0.30wt%, C≤0.08wt%, N≤0.05wt%, H≤0.015wt%, O0.08-0.15wt%, and the rest is Ti. The powder composition complies with the provisions of GB / T3620.1-2017 for TC4, Hall flow rate: ≤40s / 50g, bulk density: ≥2.2g / cm 3 , tap density: ≥2.6g / cm 3 The theoretical density of the parts prepared by SLM is 4.43g / cm 3 ;
[0015] Preferably, the use of a 240-mesh (63 μm) standard experimental sample sieve to screen the recycled powder in step S2 is to remove large particle agglomerates that are remelted and condensed in the heat-affected zone around the molten pool during the layer-by-layer printing process, thereby ensuring the particle size and fluidity of the recycled powder.
[0016] Preferably, in step S2, the recycled powder of the heat affected zone is collected, and different ratios of fresh powder and screened recycled powder are designed according to the mass fraction ratio. On the one hand, the recycled powder of the heat affected zone after the separation printing process is completed is improved, and the recovery purity of the remaining Ti-6Al-4V non-thermal conductive new powder on the substrate is improved. On the other hand, the utilization rate of Ti-6Al-4V powder in the entire part printing process is increased on the basis of ensuring the preparation quality.
[0017] Preferably, the use of an electron scanning microscope in step S3 is to observe the sphericity, surface smoothness, and the stacking state between particles of the fresh powder and the recycled powder under a high-power microscope, and the use of a laser particle size analyzer is to obtain the change in particle size and the distribution range of the particle size of the fresh powder and the recycled powder through shading analysis.
[0018] Preferably, the building chamber in step S4 is a closed space, and high-purity argon is filled as a protective gas before the printing process begins. The gas flow rate is set to 20-50 L / min, and the oxygen content in the building chamber is ensured to be less than 0.02% during the entire preparation process.
[0019] The beneficial effects of the present invention are:
[0020] (1) The present invention adopts the SLM process to perform powder bed melting additive manufacturing on a Ti-6Al-4V recycled mixed powder substrate. On the one hand, it solves the problem that the Ti-6Al-4V alloy has poor thermal conductivity, strain hardening tendency and high oxygen affinity, and is not suitable for traditional manufacturing processes such as forging, casting and rolling; on the other hand, the proportion of mixed powder is used to prepare parts, which reduces the cost of metal powder raw materials and improves the utilization rate while ensuring the performance requirements of the formed parts.
[0021] (2) The powder proportion mixing process described in the present invention is based on the combination of numerical simulation and experiment. The discrete element method (DEM) is used to establish a three-dimensional powder bed model close to the actual powder filling density (0.4), and the powder layer size is 1000μm*400μm*60μm. Considering the complex thermal physical mechanisms in SLM, such as heat conduction, heat radiation, heat convection, evaporation, melting and solidification, Air entrainment, Density evaluation, Gravity and non-inertial reference frame, Heat transfer, Solidification, Surface tension, Viscosity and turbulence solvers are used in parallel to restore the actual printing process to the greatest extent.
[0022] (3) Compared with the commonly used powder coating thickness of 20 μm-30 μm, the 40 μm printing layer thickness of the present invention, on the one hand, improves the preparation efficiency of the additive process; on the other hand, increases the utilization rate of large-particle powder during the printing process, improves the average particle size composition of the recycled powder after printing, and improves the sustainable use of the recycled powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1This is an additive manufacturing flow chart of a selective laser melting titanium alloy powder recycling process described in Example 1;
[0024] Figure 2 A three-dimensional randomly distributed powder bed model diagram with a packing density of 0.4 was created for Example 1 using the discrete element method (DEM) with reference to the actual powder characteristic parameters;
[0025] Figure 3 This is a simulation molten pool result diagram of the SLM powder bed laser molten pool using thermodynamic finite element simulation software in Example 1;
[0026] Figure 4 The electron scanning microscope surface morphology images of the new powder and the recycled powder in Example 1; (a) is the new powder, (b) is the splashed powder, (c) is the remelted powder in the heat affected zone, and (d) is the enlarged detail of the remelted powder;
[0027] Figure 5 The particle size distribution curves of the new powder and the recycled powder described in Example 1;
[0028] Figure 6 This is a solid block sample image printed with 0% and 20% mixed powders in group 1 parameters as described in Example 1;
[0029] Figure 7 This is a solid block sample image printed with the 20% mixed powder in Example 1 at the parameters of Group 2 to Group 11;
[0030] Figure 8 This is a three-dimensional topographic image of the upper surface of a solid block sample printed with group 1 parameters using the 0% and 20% mixed powders described in Example 1.
[0031] Fig. 9 The three-dimensional topographic image of the upper surface of the solid block sample printed with the parameters of group 2, group 4 and group 6 of the 20% mixed powder described in Example 1;
[0032] Fig.10 This is a three-dimensional topographic image of the upper surface of a solid block sample printed with parameters in Group 7, Group 9, and Group 11 using the 20% mixed powder described in Example 1. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0034] Example 1: A selective laser melting titanium alloy powder recycling process, the specific steps are as follows:
[0035] S1: Using the discrete element method (DEM), the particle size range, Poisson's ratio, shear modulus, particle density and other physical properties are limited. Through the method of diameter scaling replication and Cartesian coordinate system positioning, a three-dimensional randomly distributed powder bed model close to the actual powder filling density (0.4) is established. The powder bed size is 1000μm*400μm*60μm, such as Figure 2 As shown, the bottom is a rigid structure of the same size.
[0036] S2: The powder bed model is imported into FLOW-3D for finite element secondary development simulation. Considering the complex thermal physical mechanisms of the SLM process, such as heat conduction, heat radiation, heat convection, evaporation, melting and solidification, the solvers such as Air entrainment, Density evaluation, Gravity and non-inertial reference frame, Heat transfer, Solidification, Surface tension, Viscosity and turbulence are used in parallel in the solution environment to restore the actual printing process to the greatest extent. The laser heat source conforms to the Gaussian distribution and irradiates the upper surface of the powder layer in the form of a surface heat source:
[0037]
[0038] Where: q(r) is the heat flux density of a point within the radius of the Gaussian laser beam, P is the total laser power, ɑ is the laser absorptivity of the powder, ω is the radius of the Gaussian laser beam, and r is the distance between a point within the radius of the Gaussian laser beam and the center of the heat source at time t.
[0039] The heat source program and boundary conditions are compiled based on the above physical phenomena, and the convection field and temperature field under the simulated dynamic molten pool are analyzed, such as Figure 3 According to the heat affected zone size data and 70% molten pool overlap rate, appropriate process parameters are selected, including laser power, scanning speed, spot diameter and scanning spacing, and the process window with a molten pool depth greater than 40μm (to ensure complete bonding between layers) is selected as shown in Table 1.
[0040] S3: According to the corresponding heat-affected zone data described in S2, the Ti-6Al-4V powder that has undergone a cycle of thermal cycling in the construction area during the selective laser melting preparation is collected, and the recycled powder is sieved using a 240-mesh (63μm) standard experimental sample sieve to remove large particle agglomerates that are remelted and condensed in the heat-affected zone around the molten pool during the layer-by-layer printing process to ensure the particle size and fluidity of the recycled powder. The two powders are analyzed and tested, and the surface morphology of the powder is as follows: Figure 4 As shown, the powder size changes as Figure 5 As shown, the connection between recycled powder characteristics, process parameters and forming performance is taken as the theoretical innovation of the present invention, and the fresh powder and the sieved recycled powder are mixed evenly with a powder mixer according to the mass fraction ratio of 0% and 20% for later use.
[0041] S4: EOS M100 was used as the printing device, Ti-6Al-4V alloy plate was used as the rigid substrate, ethanol was used to clean the stains, and after being dried by a hair dryer, it was fixed in the build chamber, the initial position of the rigid scraper was adjusted, and the thickness parameters of the base powder layer were controlled. In order to analyze the influence of laser energy input on the preparation performance when the thermophysical properties of the recycled powder changed, two proportions of mixed powder were used as raw materials in this experiment, and the parameters were adjusted corresponding to the different groups of process parameters in Table 1. The building samples followed a scanning strategy involving a 67° rotation between layers. A cube with a side length of 10 mm was made to study the surface morphology and microstructural evolution.
[0042] S5: Use wire cutting machine to separate solid samples from rigid substrates, where the solid samples prepared under group 1 parameters are as follows: Figure 6 As shown, Group 2-11 parameters prepare entities such as Figure 7 The surface morphology of the solid sample was observed by optical microscope, and the three-dimensional images of the upper surface of different groups of solid blocks were obtained as shown in Figure 8 - Fig.10 The surface roughness of the solid block was measured by white light diffractometer and the line roughness data was shown in Table 2. The goal is to optimize the process parameters and use the recycled powder to obtain a parameter combination of a sample with a relative density of ≥99%, a hardness of ≥350HV, a surface roughness of Ra≤12.5μm, and a metallographic structure of acicular martensite. The parameter combination includes laser power, scanning speed, powder thickness, and scanning spacing.
[0043] In the surface morphology and particle size distribution data of new powder and recycled powder in S3, (a) is Ti-6Al-4V fresh powder, with a wide distribution of particle sizes and fewer fine particles. Some small particles will be adsorbed around large particles. Because there is no bonding relationship between the two, they are completely separated by external factors, and have almost no effect on the packing density and fluidity of the powder bed. Under high-energy-density laser irradiation, the surface temperature of the molten pool exceeds its boiling point and metal evaporates, which gathers above the molten pool to form recoil pressure, causing the molten droplets in the laser molten pool to sputter. According to the principle of minimum surface energy, these droplets cool and solidify due to surface tension during sputtering to form spherical splashing particles with extremely high roundness, such as Figure 4 As shown in (b), the size distribution of the splashing powder is narrow, with no large-sized agglomerates or fine particles. However, when it falls back to the powder bed, some satellite particles will adhere to the surface due to incomplete cooling. If they are separated by external force, pits or irregular protrusions will be formed on the surface of the particles. The particles shown in (c) and (d) are thermal cycle powders distributed in the heat-affected zone around the laser melting pool. Due to their proximity to the melting pool, they absorb heat and partially melt. The small particles melt to a higher degree and adhere to the surface of the semi-molten large particles to form broken and irregular agglomerates. These agglomerated large particles are firmly bonded, and separation by external force will result in broken irregular particles, which will seriously affect the packing density and fluidity of the powder layer. The recycled powder collected in this experiment is composed of splashing particles in the heat-affected zone and thermal cycle powder, of which splashing particles account for a very small proportion.
[0044] The particle size distribution data of the new powder and the recycled powder in S3 are as follows: Figure 5 As shown, compared with the powder SEM morphology, the change in powder size of the recycled powder is more intuitive. Compared with the new powder, the overall particle size distribution of the recycled powder is narrower, the volume fraction of particles with a particle size less than 30μm is greatly reduced, and the volume fraction of particles larger than 50μm is increased. Overall, the cumulative distribution proportion of the recycled powder in (b) shows an increasing trend in particle size, and the growth trend of small particles is the most significant. The cumulative distribution proportion reaches 10%, and the corresponding particle size increases from 19.70μm to 26.72μm. This is because of the remelting effect, the small particles of powder melt first and sinter.
[0045] The SLM experiment in S4 was prepared using an EOS M100 (EOS, Germany) machine equipped with a Yb-fiber laser with a wavelength of 1060nm and a maximum power of 200w (laser spot size 40μm). During the preparation process, the inert gas valve was continuously opened, high-purity argon was filled, and the protective gas flow rate was set to 20-50L / min to ensure that the selective laser melting printing process was carried out in an argon atmosphere with an oxygen concentration of less than 0.02%.
[0046] The surface morphology and roughness of the formed sample in S5 were tested, and it was found that under the default parameters of the printing equipment (such as the parameters of Group 1 in Table 1), the layer thickness of 20 μm removed larger particles, increased the packing density of the powder bed, reduced the bonding pore defects between layers during the laser melting process, and reduced the bonding effect of the unmelted powder, so that the prepared sample had low porosity and a smoother surface.
[0047] In S5, Figure 7 The results show that when 20% mixed powder is used as raw material for printing, the default parameters are no longer applicable, and when the average particle size of the recycled powder increases, the 20μm layer thickness actually reduces the utilization rate of the recycled powder on the powder bed, because the larger particles are scraped away by the rigid scraper, which further increases the proportion of large particles in the remaining powder, greatly reducing the reusability of the remaining powder. However, in the process of parameter optimization of the present invention, it was found that when the layer thickness increased to 40μm, although the forming efficiency and the utilization rate of the recycled powder were improved, the surface of the sample became rougher at low scanning speeds, such as Fig. 9 and Fig.10 The surface roughness morphology at a scanning speed of 600 mm / s is uneven and has large drop fluctuations, indicating that there are protrusions and deep pits on the surface of the sample. This is because the laser energy density is high per unit time, the molten pool expands, the cooling rate is low, the powder bed around the molten pool collapses, and the unmelted powder increases, which can be inferred that the interlayer bonding is poor. Fig. 9 and Fig.10 The surface roughness changes at the scanning speed of 800mm / s-1000mm / s show that with the increase of scanning speed, the laser energy density tends to the optimal value, the sample layers are closely bonded, and the bonding defects caused by powder collapse are reduced. The sample surface tends to be smooth and is close to Figure 8 The surface quality of the sample at a low layer thickness of 20 μm indicates that the present invention has achieved corresponding results in optimizing the process parameters of the mixed powder, which can be seen from the changes in the surface roughness data Ra of the sample in Table 2.
[0048] Table 1 Process parameters used to prepare the samples
[0049]
[0050] Table 2 Surface roughness of prepared samples
[0051]
[0052] The above are merely embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and changes. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A selective laser melting titanium alloy powder recycling process, characterized in that: The specific steps include: S1: Analyze the thermal physical mechanism, determine the process parameters, and select the process window by creating and simulating a 3D powder bed model; S2: According to the heat-affected zone size data, Ti-6Al-4V metal powder that has undergone a period of thermal cycle in the construction area of the selective laser melting preparation is collected, and the recycled powder is sieved using a 240-mesh standard experimental sample sieve. Based on the total mass of the collected recycled powder, the recycled powder is mixed in a powder mixer according to the mass fraction ratio of 0% and 20% of the total mixed powder. S3: Use an electron scanning microscope and a laser particle size analyzer to test fresh powder and recycled powder, and adjust the selection range of printing parameters based on the differences in various characteristics of fresh powder and recycled powder in the test results; S4: In a 3D printing device whose printing space is a closed building cabin, a Ti-6Al-4V alloy plate is used as a rigid substrate, the basic powder layer thickness parameter is controlled by adjusting the position of a rigid scraper, mixed powders of different proportions are added in groups as raw materials, and different process parameter combinations in the selected process window are combined. High-purity argon is used as an inert protective gas, and the solid sample printing is started by laser melting the powder layer; S5: Use a wire cutting machine to separate the solid sample, observe the surface morphology of the solid sample through an optical microscope, grind, polish and corrode the solid sample, observe the pores and metallographic structure, and optimize the process parameters. Use a mixed powder with a ratio of 0%-20% to obtain a sample with a relative density ≥99%, a hardness ≥350HV, a surface roughness Ra≤12.5μm, and a metallographic structure of acicular martensite. Determine the parameter combination of laser power, scanning speed, powder thickness and scanning spacing.
2. The selective laser melting titanium alloy powder recycling process according to claim 1 is characterized in that: The S1 is specifically: S1.1: Use the discrete element method to refer to the actual powder characteristic parameters to create a three-dimensional randomly distributed powder bed model that meets the actual powder packing density range. The powder bed size is that the width is greater than the spot diameter of the printing device, the height is consistent with the thickness of the printed powder layer, the length is unlimited, and the bottom is set to a rigid structure of the same size; S1.2: Import the powder bed model into the thermodynamic simulation software for finite element secondary development simulation, and use Gaussian heat source as the laser heat source; S1.3: Use multiple temperature field solvers in parallel during the simulation process to truly restore the actual printing process; S1.4: Analyze and simulate the convection field and temperature field under the dynamic molten pool, determine the process parameters of laser power, scanning speed, spot diameter and scanning spacing according to the heat affected zone size data and the molten pool overlap rate of 60%-80%, and select the process window where the molten pool depth is greater than the set powder layer thickness data.
3. The selective laser melting titanium alloy powder recycling process according to claim 1 is characterized in that: The particle size of the Ti-6Al-4V metal powder is in the range of 15-53 μm, the chemical composition of the powder is Al 5.5-6.75wt%, V 3.5-4.5wt%, Fe≤0.30wt%, C≤0.08wt%, N≤0.05wt%, H≤0.015wt%, O 0.08-0.15wt%, and the rest is Ti. The powder composition conforms to the provisions of GB / T3620.1-2017 for Ti-6Al-4V, Hall flow rate: ≤40s / 50g, loose density: ≥2.2g / cm 3 , tap density: ≥2.6g / cm 3 .
4. The selective laser melting titanium alloy powder recycling process according to claim 1 is characterized in that: In step S3, the electron scanning microscope is used to observe the sphericity, surface smoothness, and the stacking state between particles of the fresh powder and the recycled powder under a high-power microscope. The laser particle size analyzer is used to obtain the change in particle size and the distribution range of the particle size of the fresh powder and the recycled powder through shading analysis.
5. The selective laser melting titanium alloy powder recycling process according to claim 1, characterized in that: In the closed building chamber in step S4, the gas flow rate is set to 20-50 L / min, and the oxygen content in the building chamber is ensured to be less than 0.02% during the entire preparation process.